SCREENING OF THE EFFECTS OF PLANT ALKALOIDS ON THE CONTRACTILE ACTIVITY OF RAT TRACHEAL SMOOTH MUSCLE CELLS (British Journal of Global Ecology and Sustainable Development, 2023)
The article studies the effect of plant alkaloids 1-O-benzoylnapellin, zongorin, dihydroathysine and 6-benzoylheterathisine on the contractile activity of rat tracheal smooth muscle cells. It was found that 1-O-benzoylnapellin, dihydratizine, 6-benzoylheterazine and zongorin under conditions of КСl -induced contracture exhibit a relaxant effect, which may be due to their interaction with potential-dependent Са2+ channels of plasma membranes and suppression of the entry of Са2+ ions into the MMC of rat trachea.